C4d immunostaining is an independent predictor of cardiac allograft vasculopathy and death in heart transplant recipients. (27th March 2015) - Luk, Adriana; Alba, Ana Carolina; Butany, Jagdish; Tinckam, Kathryn; Delgado, Diego; Ross, Heather J.
Summary Antibody‐mediated rejection (AMR) occurs in 10–20% of patients after heart transplantation. C4d immunostaining is one parameter used in its diagnosis. This study aimed to determine whether C4d staining has prognostic significance for mortality, coronary allograft vasculopathy (CAV), cell‐mediated rejection (CMR), and graft dysfunction in patients post‐transplantation. Consecutive patients receiving an endomyocardial biopsy between 2007 and 2008 were selected. Left ventricular function, angiography, episodes of AMR/CMR, and death were noted. C4d was graded from 0 to 3 (immunostaining). Cox proportional models (recurrent events analysis) were used to evaluate C4d staining with mortality, graft dysfunction, CAV (≥grade 2), and episodes of ≥2R‐CMR. We analyzed 2525 biopsy specimens (n = 217). During a follow‐up of 4.5 ± 2 years, 35 died, 49 had graft dysfunction, seven had ≥grade 2 CAV, and 95 episodes of CMR occurred. A one‐grade increase in C4d staining was associated with an increase in mortality (HR 1.57; 95% CI 1.0–2.5), a higher risk of CAV (HR 2.4, 95% CI 1.04–5.4), and a trend toward graft dysfunction (HR 1.42; 95% CI 1.0–2.09). C4d was not associated with CMR. C4d immunostaining was a significant predictor of CAV and death but not subsequent episodes of CMR. There was also a trend toward increased graft failure.